METODOLOGI STUDI ISLAM (TELAAH KONSEP DASAR, URGENSI, TUJUAN DAN METODE PEMAHAMAN AJARAN ISLAM DI INDONESIA) - Nurhayana; Abdul Muis; Abbas (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The study of Islamic studies methodology is highly relevant for discussing the basic concepts, urgency, and objectives of Islamic studies methodology, and outlining methods for understanding Islamic teachings in the context of pluralistic and dynamic Indonesian society. This study is expected to provide a more comprehensive and in-depth understanding of Islam and encourage the emergence of moderate, rational, and nationally beneficial religious patterns. This study aims to understand the basic concepts of Islamic studies methodology, as well as to understand the urgency of studying it, to understand the objectives of Islamic studies methodology, and to understand the various scientific approaches (social, humanities, and theological) used in understanding Islam. This study uses a qualitative approach with a library research method, namely examining various classical and contemporary literature relevant to Islamic studies methodology, both from a normative-theological and historical-sociological perspective. The results of the study indicate that the basic concept of Islamic studies methodology is a systematic epistemological foundation that functions as a framework for understanding Islam scientifically, dynamically, and comprehensively. The sources of Islamic studies are the Qur'an, Hadith, and ijtihad (Ijma and Qiyas). The urgency of Islamic studies lies in its function as an instrument of social transformation, enabling people to understand Islam holistically (kaffah) and avoid partial understandings and extreme attitudes. The primary goal of Islamic studies is to deeply and systematically understand the essence, core teachings, and basic principles of Islam in order to develop noble morals and a well-rounded personality within the individual. The method of understanding Islamic teachings in Indonesia has unique characteristics, combining cultural openness with a spirit of pluralism within the framework of the Unitary State of the Republic of Indonesia.